2022
DOI: 10.1002/jum.16117
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of Soft Tissue Calcifications in the Head and Neck Region Detected on Panoramic Radiographs

Abstract: Objective The aim of this study is to present a comparison between panoramic radiographs and USG imaging with a focus on revealing the advantages of USG over radiographs, and to show the distribution of calcifications detected in USG by considering the age and gender. Methods A total of 148 patients with soft tissue calcifications as seen on panoramic radiographs were examined with USG imaging. Sialoliths, carotid artery calcifications, tonsilloliths, phleboliths and lymph node calcifications were examined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Amongst patients 54 years and older, the prevalence reported was 21.68% [20], and amongst African American adult females, the prevalence reported was 24% [21]. The accuracy of PRs in the identification of CAC remains inconclusive [13,22,23]. A study of carotid endarterectomy with stenosis ≥ 75% in the internal carotid artery showed that 99% of the plaques were calcified and up to 84% of them were detected on PRs preoperatively [24].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst patients 54 years and older, the prevalence reported was 21.68% [20], and amongst African American adult females, the prevalence reported was 24% [21]. The accuracy of PRs in the identification of CAC remains inconclusive [13,22,23]. A study of carotid endarterectomy with stenosis ≥ 75% in the internal carotid artery showed that 99% of the plaques were calcified and up to 84% of them were detected on PRs preoperatively [24].…”
Section: Introductionmentioning
confidence: 99%